Discovery of the Late Jurassic-Early Cretaceous Lamprophyres in Western Songliao Basin of Northeast China and Their Constraint on Regional Lithospheric Evolution - Yu, Taiji; Wang, Pujun; Zhang, Yan; Gao, Youfeng; Chen, Chongyang (Frontiers in Earth Science, 2022)
Contrary to the commonly accepted notion that the lithosphere in NE China thinned from the Late Jurassic through to the Early Cretaceous period, we report the discovery of a thickening episode in the backdrop of this long-term thinning. A series of lamprophyre dikes have been recently discovered in the Tuquan Basin of the western Songliao Basin that have been dated to 156.0 ± 2.3 Ma, 132.9 ± 1.2 Ma, and 126.2 ± 2.5 Ma by using the zircon U–Pb technique. These lamprophyres are subdivided into biotite orthoclase lamprophyre (BOL) from the Late Jurassic and quartz magnetite lamprophyre (QML) from the Early Cretaceous. The BOL and QMLs are shoshonite and calc-alkaline in series, are characterized by large amounts of FeOT, TiO2, MgO, and Mg#, and are rich in LREEs and LILEs but poor in HREEs and HFSEs. They have high ratios of (La/Yb)N, La/Ta, La/Nb, Th/Y, Ba/Nb, Ba/Ta, and Ba/Th, and low ratios of Zr/Ba, La/Sm, and Nb/Zr. These features collectively point to the derivation of dike magmas from the partial melting of the enriched lithospheric mantle that had been previously metasomatized by subduction-related fluids. The BOL has high ratios of Rb/Sr (0.42) and K/Yb*1000 (28.3), and low ratios of Ba/Rb (13.5) and Dy/Yb (2.35), suggesting the derivation of magma from a high degree of partial melting of the phlogopite-bearing lherzolite mantle in the spinel–garnet transition zone at a depth of about 60 km. The QMLs have low ratios of Rb/Sr (0.02–0.06) and K/Yb*1000 (8.13–19.73), and high ratios of Ba/Rb (17.6–42.6) and Dy/Yb (3.48–4.09), indicating that the magmas were derived from a low degree of partial melting of the lherzolite mantle in the garnet zone at a depth of ca. 85 km. The younger QML (126.2 ± 2.5 Ma) has a lower Dy/Yb ratio (3.48–3.92) than the older QML (132.9 ± 1.2 Ma), with a Dy/Yb ratio of 4.09 implying that the younger magma was formed at a shallower depth of the mantle (<85 km) than the older one. These observations indicate that in 156–132 Ma, the lithosphere thickened by approximately 25 km at a rate of approximately 1.0 km/Myr. This is used to propose a model of geodynamic evolution in three stages.